Pertunjukan Bunraku dan Wayang Golek - Tambunan, Nova (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2015)
Tambunan, Nova Cristiani. 2014. “Comparison of Structural Elements Supporting Performances Bunraku with Wayang Golek”. Thesis. Departement of Japanese Studies Faculty of Humanities. Diponegoro University. The first Advisor Redyantoo noor, M.Hum. The Second Advisor Yuliani Rahmah, M.Hum. Keywords : Bunraku, Wayang Golek, sturctural of elements supporting performances, social function. This thesis research about Comparison of Structural Elements Supporting Performances Bunraku with Wayang Golek. Problems researching is What is elements structure of Bunraku with Wayang Goleks performances, Similarities and differences in the function of the Bunraku with Wayang Golek. The purpose of this research is to analyze the differences and similarities elements of Bunraku performances well as social functions with Wayang Golek. The methods used in this research are comparative literature as a principal theory that is compare the elements performances with social functions, and theory of the structure of the performing arts as a supporter of the theory in this research. The result of this research show that Bunraku with Wayang Golek performance art has similarities and differences in the performance elements of and social function.